Playing school with a screen and a keyboard - Kalman, Judith; Hernández Razo, Oscar Enrique (Education Policy Analysis Archives, 2013)
National and multilateral government agencies and popular narrative promote the idea that the use of information, communication and design technology (ICT-D) in education transform teaching. It is argued that these changes will help students become part of a “new economy” based on the use of ICT-D and characterized by “increased productivity”, “collaboration” and “flexibility.” This article questions this view of technological determinism by presenting an analysis of classrooms in a working class area of Mexico City where young people and adults are being taught to use the computer. Using a sociocultural approach based on the concept of situated practice, we show how some of the decisions and directions of the instructors in computer classes for youth and adults respond to educational traditions, notions of basic education for adults, and beliefs about learning that promote mechanical exercises and repetition. The discussion posits teachers’ beliefs and actions are social constructions rather than individual choices or shortcomings by presenting teaching materials provided by the public agency responsible for adult education in Mexico.